Service Quality and User Complaints in International Vaccination Services: A Case Study - Nurwakhid Yulianto; Maryana Maryana (Genius Journal, 2027)
Introduction: International vaccination services are part of public health services that support international mobility. As a service provider, Port Health Office is required to deliver high-quality services oriented toward user satisfaction. However, complaints are still found, indicating a gap between users’ expectations and the services received. Objective: This study aims to analyze complaints from users of international vaccination services at BKK Pangkalpinang and their relationship with service quality. Method: This study employed a qualitative approach with a case study design. Informants were selected purposively and consisted of service users, service officers, and management representatives. Data were collected through in-depth interviews, observations, and document review, and were analyzed thematically using the Donabedian framework, which includes structure, process, and outcome. Data trustworthiness was ensured through triangulation and member checking. Result: The findings indicate that user complaints are influenced by structural and process-related aspects of service delivery. Structural issues include limitations in facilities and the number of service personnel, while process-related issues involve waiting time, clarity of service flow, and staff communication. These complaints have an impact on user dissatisfaction. Conclusion: The study concludes that improving service quality requires strengthening structural and process components, as well as enhancing an effective complaint-handling mechanism.